Stan gotowości zamków pomorskich i wielkopolskich w świetle lustracji Królewszczyzn z poł. XVI w - PLEWCZYŃSKI, Marek (Historia i Świat, 2014)
The surveys of the royal real properties in Pomerania and Greater Poland from 1564 to 1565 include descriptions of fortresses. A three person committee evaluated the state of particular castles. Some of them were in a bad state, especially those in Człuchów and Gniew. Fortresses in Tuchola, Świeć, Grudziądz, Brodnica, and Bratian had been repaired just before the survey was completed. The fortresses which previously had belonged to The Teutonic Order were renovated when the survey was undertaken. Castles in Greater Poland had been built during the reign of Casimir the Great and thus required serious repairs. Castles in Brzesko (Brrześć ?) and Inowrocław areas were in a better state than the castles at the Silesian border. Moreover, the amount of firearms was greater in the southern part of Poland than in the northern one. However, as far as manpower and supplies of garrisons are concerned, they were insufficient in the whole country.. In sum, by the time of the surveys most of the inspected fortifications were out of date.